Ebenezer Howard’s Garden City Idea and the Ideology of Industrialism - Jean-Yves Tizot (Cahiers Victoriens et Edouardiens)
In Tomorrow! A Peaceful Path to Real Reform (1898) Ebenezer Howard proposed a blueprint for an ideal society, in which he formulated his solution to the ‘Land question’—roughly speaking, the conjoined phenomena of the overcrowding of towns and cities, and the so-called ‘rural exodus’. His was a vision of a ‘Social City’: a ‘Central City’ surrounded by six satellite towns or ‘Garden Cities’, all with limited numbers of inhabitants. The famous diagrams and maps show how complex and detailed and even fastidious Howard’s investigation of the topic of land reform had been before he ventured to publish his views on the subject. While his programme is usually known for these spatial aspects, the other core elements of the Garden City programme are actually not about planning or mapping, but about the proposed social organisation. In the introduction to his only book, Howard makes it clear that two out the three ‘proposals’ from which he initially drew inspiration were themselves influenced by the pregnant ideological template of industrialism: Buckingham’s ‘Model Town’ of Victoria and Alfred Marshall’s ‘industrial district’. Howard purported to transcend the apparent contradiction between socialism and capitalism by planting his vision firmly on the common ground of these two supposedly incompatible conceptions of society. Ebenezer Howard’s ‘Garden City’ proposal is thus arguably the most accomplished formulation of a plan for an ideal social model along the main lines of the collective psyche and experience of industrialism.